2017
DOI: 10.1155/2017/7365080
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between GSTT1, GSTM1, and GSTP1 Ile105Val Gene Polymorphisms and Environmental Risk Factors in Premalignant Gastric Lesions Risk

Abstract: The study investigated the possible influence of GSTM1, GSTT1, and GSTP1 gene polymorphisms as predisposing factors for premalignant gastric lesions as well as their interaction with H. pylori infection, gastrotoxic drugs, smoking, and alcohol consumption. In this study, 270 patients with a complet set of gastric biopsies and successfully genotyped were finally included. The GSTM1 gene polymorphism had significant contribution in mild/severe endoscopic lesions (p = 0.01) as well as in premalignant lesions (p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…MDR1 (or ABCB1) gene polymorphisms C1236T, G2677T, and C3435T were genotyped by PCR-RFLP techniques to investigate the association between the mentioned SNPs and antiepileptic drug concentrations and treatment response (7), clinical course of pediatric pulmonary arterial hypertension (8), and gastric lesions (9). Furthermore, the PCR-RFLP method was applied for analyzing the interleukin-6 SNPs and their correlations with patients' sepsis risk and severity in adult patients (10) for glutathione S-transferase (GST) SNPs in premalignant gastric lesions risk (11) and for investigation of the impact of CYP2C19 polymorphisms in platelet response to clopidogrel (12) and on severity of gastric lesions (9). Nested PCR technique is a variant of PCR that increases the specificity and efficiency of the desired amplicons by using two pairs of PCR primers (outer primers and nested primers).…”
Section: Polymerase Chain Reaction -Restriction Fragment Length Polymmentioning
confidence: 99%
“…MDR1 (or ABCB1) gene polymorphisms C1236T, G2677T, and C3435T were genotyped by PCR-RFLP techniques to investigate the association between the mentioned SNPs and antiepileptic drug concentrations and treatment response (7), clinical course of pediatric pulmonary arterial hypertension (8), and gastric lesions (9). Furthermore, the PCR-RFLP method was applied for analyzing the interleukin-6 SNPs and their correlations with patients' sepsis risk and severity in adult patients (10) for glutathione S-transferase (GST) SNPs in premalignant gastric lesions risk (11) and for investigation of the impact of CYP2C19 polymorphisms in platelet response to clopidogrel (12) and on severity of gastric lesions (9). Nested PCR technique is a variant of PCR that increases the specificity and efficiency of the desired amplicons by using two pairs of PCR primers (outer primers and nested primers).…”
Section: Polymerase Chain Reaction -Restriction Fragment Length Polymmentioning
confidence: 99%
“…Many patients with CHF use antithrombotic treatments, antiplatelet and/or anticoagulants. These drugs promote the blood loss by the entire GIT from various mucosal lesions [17,18,19,20]. Furthermore, gastrointestinal conditions that do not usually induce bleeding, frequently associate iron deficiency anemia due to impairment of iron metabolism [21].…”
Section: Discussionmentioning
confidence: 99%
“…2,12,13 Case-control or observational studies evaluating the interaction between gastric cancer and statin therapy showed a neutral effect, 14,15 while others have noticed a reduced rate of gastric cancer, [16][17][18] , or even an inverse effect.3 The present research identified a statistically significant protective role of statins (p = 0.006) against premalignant lesions in the studied population, while age over 50 years and smoking remain the most important risk factors for premalignant gastric lesions. Statin therapy might have a certain protective effect, but other factors related to the host's genetic susceptibility 19 and the complex interaction with environmental risk factors should be considered in further large models.…”
Section: Discussionmentioning
confidence: 99%